Environmental training: a systematic review of the state of the art of the theme. Issue 7 (10th June 2019) - Stefanelli, Nelson Oliveira; Teixeira, Adriano Alves; Caldeira De Oliveira, Jorge Henrique; Antonio Ferreira, Marco; Sehnem, Simone
Abstract : Purpose: The purpose of this paper is to carry out a systematic review of the state of the art of the environmental training theme and to propose a research agenda to shed light on this subject by suggesting new research in the area. Design/methodology/approach: This is a systematic review of the state of the art of the environmental training theme. Findings: The authors' main contribution is the proposal of a research agenda with 11 recommendations for future research, such as conducting research in developed countries; research focusing only on environmental training; qualitative research using case studies; research that explores the co-evolution of environmental training practices with environmental management practices and with the maturity stage of environmental management in organizations; and research that addresses all aspects of environmental training phases proposed by ISO 10015: 2001. Originality/value: This is the most recent research which conducts a systematic review of the state of the art on environmental training and proposes a research agenda with several suggestions that can guide researchers in human resources, environmental management, sustainability and supply chain management.